2006
DOI: 10.1007/s10157-005-0391-6
|View full text |Cite
|
Sign up to set email alerts
|

Focal segmental glomerulosclerosis associated with essential thrombocythemia

Abstract: Focal segmental glomerulosclerosis (FSGS) is a primary glomerular disease that is characterized by progressive proteinuria and declining renal function. Secondary FSGS is known to be associated with various diseases. However, an association of FSGS with essential thrombocythemia (ET) has been reported in few cases. We report a 76-year-old man who presented with nephrotic syndrome and hepatosplenomegaly. He had thrombocythemia after a splenectomy, which had been carried out at a nearby hospital. A renal biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
1
14
1
Order By: Relevance
“…Plasma and urine levels of platelet-derived growth factor (PDGF) are elevated in patients with myeloproliferative neoplasms62 and PDGF has been shown to enhance mesangial proliferation and fibrosis 63. Indeed, in one case of FSGS associated with essential thrombocythemia, nephrotic syndrome occurred after a sudden rise in platelet count following a splenectomy 64. Interestingly, although thrombocytosis also occurs in chronic myelogenous leukemia, FSGS has not been reported to be associated with chronic myelogenous leukemia, and plasma PDGF levels in patients with chronic myelogenous leukemia were normal 62.…”
Section: Hematological Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma and urine levels of platelet-derived growth factor (PDGF) are elevated in patients with myeloproliferative neoplasms62 and PDGF has been shown to enhance mesangial proliferation and fibrosis 63. Indeed, in one case of FSGS associated with essential thrombocythemia, nephrotic syndrome occurred after a sudden rise in platelet count following a splenectomy 64. Interestingly, although thrombocytosis also occurs in chronic myelogenous leukemia, FSGS has not been reported to be associated with chronic myelogenous leukemia, and plasma PDGF levels in patients with chronic myelogenous leukemia were normal 62.…”
Section: Hematological Malignanciesmentioning
confidence: 99%
“…Data are taken from several sources5456,5961,6472,7477,79,102–114 and are presented as numbers of specific types of paraneoplastic glomerulonephritis associated with different myeloid malignancies. Abbreviations: AML, acute myeloid leukemia; CML, chronic myelogenous leukemia; CMML, chronic myelomonocytic leukemia; ET, essential thrombocythemia; FibGN: fibrillary glomerulonephritis; FSGS, focal segmental glomerulosclerosis; IgAN: IgA nephropathy; MDS, myelodysplastic syndrome; MesPGN: mesangial proliferative glomerulonephritis; MCD, minimal change disease; MN, membranous nephropathy; MPGN: membranoproliferative glomerulonephritis; PMF, primary myelofibrosis; PV, polycythemia vera; RPGN, rapidly progressive glomerulonephritis.…”
Section: Figures and Tablesmentioning
confidence: 99%
“…Although several cases of glomerulonephritis associated with MPN have been reported, the etiologies of the renal disorders were not established (Plomley et al, Aust NZ J Med, 13:125–129, 1983; Sharma et al, Nephron, 69:361, 1995; Kanauchi et al, Intern Med, 33:36–40, 1994; Kasuno et al, Nephrol Dial Transplant, 12:212–215, 1997; Au et al, Am J Kid Dis, 34:889–893, 1999; Kosch et al, Nephrol Dial Transplant, 15:1710–1711, 2000; Oymak et al, Nephron, 86:346–347, 2000; Chun et al, Am J Nephrol, 20:344–346, 2000; Chung et al, Am J Nephrol, 22:397–401, 2002; Asaba et al, Clin Exp Nephrol, 7:296–300, 2003; Haraguchi et al, Clin Exp Nephrol, 10:74–77, 2006; Saigusa et al, J Nephrol, 19:656–658, 2006; Okuyama et al, Clin Nephrol, 6:412–415, 2007; Nishi et al, Clin Nephrol, 5:393–398, 2010; Ulusoy et al, Intern Med, 49:2477, 2010). A review of previous reports of renal biopsy cases with MPN in the English literature suggested that circulation control is important for the treatment of renal disorders that mimic glomerulonephritis in MPN.…”
mentioning
confidence: 99%
“…FSGS can also be secondary to HIV infection [15], obesity [16] and several other conditions [17,18,19]. Whatever the origin, however, FSGS follows the same basic pathologic pattern.…”
Section: Introductionmentioning
confidence: 99%